The bacterial lysate Lantigen B reduces the number of acute episodes in patients with recurrent infections of the respiratory tract: The results of a double blind, placebo controlled, multicenter clinical trial - Braido, Fulvio (Immunol Lett, 2014)
Studies in the 1970s and 1980s reported that bacterial lysates (BL) had a prophylactic effect on recurrent respiratory tract infections (RRTI). However, controlled clinical study procedures have evolved substantially since then. We performed a trial using updated methods to evaluate the efficacy of Lantigen B(®), a chemical BL. This double blind, placebo controlled, multi-center clinical trial had the primary objective of assessing the capacity of Lantigen B to significantly reduce the total number of infectious episodes in patients with RRTI. Secondary aims were the RRTI duration, the frequency and the severity of the acute episodes, the use of drugs and the number of missed workdays. In the subgroup of allergic patients with RRTI, the number of allergic episodes (AE) and the use of anti-allergic drugs were also evaluated. One hundred and sixty patients, 79 allocated to the treated group (TG) and 81 to the placebo group (PG), were enrolled; 30 were lost during the study and 120 (79 females and 38 males) were evaluated. The PG had 1.43 episodes in the 8-months of follow-up while the TG had 0.86 episodes (p = 0.036). A similar result was observed in the allergic patients (1.80 and 0.86 episodes for the PG and the TG, respectively, p = 0.047). The use of antibiotics was reduced (mean 1.24 and 2.83 days of treatment for the TG and the PG). Logistic regression analysis indicated that the estimated risk of needing antibiotics and NSAIDs was reduced by 52.1 and 30.6%, respectively. With regard to the number of AE, no significant difference was observed between the two groups, but bronchodilators, antihistamines and local corticosteroids were reduced by 25.7%, 56.2% and 41.6%, respectively, in the TG. Lantigen B significantly reduced the number of infectious episodes in patients with RRTI. This finding suggests a first line use of this drug for the prophylaxis of infectious episodes in these patients.